Clay-Shoveler Fracture in a Golfer: A Rare Sports Injury Case Report - Bari, Yunus Abdul; Amir, Muhammad Rafif (Journal La Medihealtico, 2024)
Clay-shoveler's fracture is a relatively rare stress-type avulsion fracture of the lower cervical or upper thoracic spinous processes, most commonly occurring at C7 and T1. The term of this injury comes from its historical association with manual laborers who lifted and threw big objects, as well as with scooping huge loads of clay in the early 20th centuryThe case report describes A 29 year old male experienced severe back pain after playing golf. at the time of the golf swing, the golf swing did not hit the ball but hit the ground. the patient experienced radiculopathy pain to both hands. A "pop" sound was audible in the spine at the moment of the hitting fault, and there was no paralysis in the lower limbs.The primary method for managing a clay-shoveler fracture is conservative. In most cases, traction of the rhomboid and trapezius muscles on the spinous process leads to nonunion. In rare cases if the pain persists, surgically removing the bone fragment may be a possibility.